Effect of pup out® on caspase 3 and interleukin-1B expression in pulp teeth: a paste contained jatropha, sidaguri, and melittin - Maria Tanumiharja; Arfina S. Hamid; Aries C. Trilaksana; Christine A. Rovani; Nurhayati Natsir; Juni J. Nugroho; Indrya K. Mattulada; Lukman Muslimin (DiscoverSys Inc., 2021)
Objective: To examine the expression of caspase-3 and IL-1? following application of Pulp Out® on rabbit’s pulp teeth as well as histopathology.Material and Methods: The study was conducted on the maxillary incisors rabbits. The teeth were prepared and Pulp Out® was inserted at the base of prepared cavity, then restored with RM-GIC. After 24 hours, the animals were then euthanized and processed for histopathology and immunohistochemistry evaluation.Results: Our results indicated that Pulp Out®, when administered to the pulp teeth, increased the number and diameter of blood vessels. The expression of caspase-3 and IL-1? showed similarities to the expression of commercial devitalizing agent.Conclusion: Our results revealed that Pulp Out® is a valuable devitalization agent that should be further explored for its safety before clinical application.